TAMTSIL AL MAR’AH FI MU’ALLAQAH IMRUI AL QOIS: DIROSAH SIMIYAIYAH ROLAND BARTES - Hakim, Arief Rahman; Roziki, Khafid; Faisol, M. (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
The aim of this research is to know the representation of women in the poetry of Imru' al-Qays, based on the assumption that not all women in the pre-Islamic era lived without meaning, individually and socially. The researchers took Imru' al-Qays's commentary as the subject of the research because it contains many descriptions of women. It used the qualitative research method, based on the approach of Roland Barthes' semiotic theory. The main data source is the Muallaqa Imru' al-Qays. As for the secondary data sources from the book, periodical and other journals related to the research topic. The data analysis covers three stages, description, reduction, and conclusion. It employed semiotics focusing on the reception and sources of messages. It largely depends on the researchers’ ability to interpret text or references that can be related to ideological, cultural, moral and spiritual values.  The result shows that the women in the poetry are portrayed with beautiful descriptions that indicate the high and honor of their position and they receive good treatment in their family.